Examining Technology Acceptance in Learning and Teaching at a Historically Disadvantaged University in South Africa through the Technology Acceptance Model - Clever Ndebele; Munienge Mbodila (MDPI AG, 2022)
The exponential growth in the use of technology for learning and teaching in the higher education sector has imposed pressure on academics to embrace technology in their teaching. The present study sought to examine factors underlying technology acceptance in learning and teaching at a historically disadvantaged university in the Eastern Cape Province of South Africa. Premised on the mixed methods approach and undergirded by the Technology Acceptance Model (TAM), both a pre-coded and an open-ended questionnaire were used to collect data. Data from the pre-coded questionnaire were analysed through the descriptive statistical approach. The qualitative data from the open-ended questionnaire were analysed through content analysis. The study found that most academic staff believe and see the value that ICTs bring in their teaching and learning practices. In addition, they are aware that technology use in education improves learning and teaching, and they are willing to embrace the use of technology to improve their practices. Based on the findings, we recommend intensification of lecturer training in the use of technology for teaching and learning to enable them to embrace it in their teaching practice. Furthermore, the institution needs to put in place support systems for academic staff to empower them to have continuous access to devices and internet connection for technology integration in teaching and learning. We recommend establishment of e-learning communities of practise in the university that will allow lecturers to assist each other as well as share best practices in the use of technology for teaching and learning.